Signal and Information Processing, Networking and Computers Proceedings of the 3rd International Conference on Signal and Information Processing, Networking and Computers (ICSINC) (Lecture Notes in Electrical Engineering,, 2018)
This proceedings book presents the latest research in the fields of information theory, communication system, computer science and signal processing, as well as other related technologies. Collecting selected papers from the 3rd Conference on Signal and Information Processing, Networking and Computers (ICSINC), held in Chongqing, China on September 13-15, 2017, it is of interest to professionals from academia and industry alike. .